2023
DOI: 10.21037/qims-22-186
|View full text |Cite
|
Sign up to set email alerts
|

Improving image quality and resolution of coronary arteries in coronary computed tomography angiography by using high-definition scans and deep learning image reconstruction

Abstract: Background Coronary computed tomography angiography (CTA) has been increasingly used to identify the degree of coronary artery stenosis and plaque lesions in vessels. This study evaluated the feasibility of using high-definition (HD) scanning with high-level deep learning image reconstruction (DLIR-H) to improve the image quality and spatial resolution when imaging calcified plaques and stents in coronary CTA as compared to the standard definition (SD) reconstruction mode with adaptive statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…We applied DLIR to CTPA studies in suspected PE. Our results are in line with those that have been described for various cardiovascular CT applications including coronary CTA 19 23 , CT for planning of transcatheter aortic valve repair 24 , 25 , CT of the aorta 26 , head and neck CT angiography 27 and triple-rule-out CT 28 . In the field of thoracic imaging, several previous studies have investigated the value of DLIR with regards to pulmonary imaging and lung nodule detection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We applied DLIR to CTPA studies in suspected PE. Our results are in line with those that have been described for various cardiovascular CT applications including coronary CTA 19 23 , CT for planning of transcatheter aortic valve repair 24 , 25 , CT of the aorta 26 , head and neck CT angiography 27 and triple-rule-out CT 28 . In the field of thoracic imaging, several previous studies have investigated the value of DLIR with regards to pulmonary imaging and lung nodule detection.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, DLIR has been shown to improve image denoising and increase image quality beyond the levels of achieved with iterative reconstruction techniques in various cardiovascular CT applications including coronary CTA 18 23 , CT for planning of transcatheter aortic valve repair 24 , 25 , CT of the aorta 26 , head and neck CT angiography 27 and triple-rule-out CT 28 . There are very limited data about DLIR in CTPA despite this being one of the most commonly performed cardiovascular CT examinations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that CCTA reconstructed by different vendor techniques based on deep learning can achieve higher image quality than can traditional image reconstruction (FBP and IR) ( 23 - 25 ), but no previous studies have evaluated the effect of using specific DLIR algorithms on HD-standard scanned CCTA images. One recent study evaluated coronary artery images acquired with the HD-standard mode and the DLIR algorithm ( 26 ), but the sample size of the study was insufficiently large (only four stents were evaluated), and STND scan mode was not used for comparison. In contrast, our study evaluated 76 stents with a greater array of evaluation parameters and used the STND scan mode of comparison; in other words, our study further complemented and confirmed these findings.…”
Section: Discussionmentioning
confidence: 99%